Visual framing by social movement organisation towards political participation in Malaysia: an analysis on the BERSIH Movement / Mohd Firdauz Mohd Fathir - Mohd Fathir, Mohd Firdauz (2022)
This multi-method qualitative study examines the visual framing towards political participation by one of the largest political social movements in Malaysia, the BERSIH movement, within a social media setting. The recent attention on the growing trends of social movements within the political atmosphere in Malaysia is on the phenomenal record usage of the multimodal nature of social media platforms as framing tools to spread ideology. Building on the existing work on visual framing, five research objectives guides this research : (1) To explore the visual portrayal of issues on the BERSIH Facebook Page. (2) To identify the styles and visual techniques used in the visual portrayal of issues on BERSIH Facebook Page. (3) To interpret the underlying meaning of visual frames that can identified from the visual portrayal of issues on the BERSIH Facebook Page (4) To analyse the outcome of styles and visual techniques that can be identified from the visual portrayal of issues on the BERSIH Facebook Page. (5) To understand the overall visual framing on the BERSIH Facebook Page. This study was guided by two theories: Agenda Setting Theory and Visual Framing Theory. Using a phenomenology approach, a qualitative visual content analysis was done to a sample of 59 selected photos as well as in-depth interviews with 10 informants which includes political experts, visual experts, and key persons involved in the movement. Data analysis was conducted simultaneously with data collection and the Atlas.ti 8.4.4 software was used in the process of coding. Thematic analysis were used to analyse the data. The findings showed that the main forms of visuals used were photos of protesters, followed by photos of significant individuals. The findings also showed the main framing that was highlighted was 'solidarity' followed by 'call for action' in the form of direct and symbolic visuals. Elements of negative emotions like anger and disgust were also found to be a regular pattern within the visuals. However, cool factor and portrayal of neutrality can also invite likability towards the movement. Apart from that, a good framing strategy like good timing and simplicity would contribute to the success of visual framing. The findings provide a basis for understanding the use of visual framing by social movement organizations in Malaysia. By understanding these visual frames, the findings will act as a reference to social leaders and organisation who wishes to develop a sustainable strategy for stimulating engagement effectively through visual.